Efficacy of Vitamin C in Ameliorating Ochratoxicosis in Broiler Chicken - Singh, Ram; Mandal, Asit Baran (Indian Journal of Animal Nutrition, 2018)
The present study was undertaken to evaluate the efficacy of vitamin C in ameliorating ochratoxicosis in broiler chickens. Day-old broiler chicks (n=240) were divided into 6 treatment groups (T1- control (Basal diet); T2- T1 + 150 ppb OTA; T3-T1 + 100 mg vitamin C-VC; T4- T1 +200 mg VC; T5- T2 + 100 mg VC; T6- T2 + 200 mg VC per kg diet). Each diet was fed to 5 replicated groups of 8 birds each from 0 to 42 days of age. During overall growth period (0-6 weeks), the BWG of control group (T1) was higher (P<0.05) than that of toxin fed group (T2). The BWG in T5 and T6 was higher (P<0.05) than that of toxin fed group (T2) but lower (P<0.05) than that of control. The feed intake did not vary significantly among various treatment groups. The FCR in control group (T1) was lower (P<0.05) than that of T2. The FCR in other treatment groups (T3 to T6) was statistically similar to that of control. The relative weight of liver and kidney in control group (T1) was lower (P<0.05) than that of ochratoxin fed group (T2). The relative weight of bursa of Fabricius in control group (T1) was higher (P<0.05) than that of T2. The total serum protein and cholesterol content of control group (T1) was higher (P<0.05) than that of T2. The uric acid and alkaline phosphatase values of control group (T1) were lower (P<0.05) than that of T2. Supplementation of vitamin C at any level to the ochratoxin contaminated diet partially ameliorated the adverse effects of ochratoxicosis on relative organ weights and biochemical parameters. It was concluded that inclusion of 100 mg vitamin C per kg diet to the ochratoxin (150 ppb) contaminated feed partially ameliorated the adverse effects of ochratoxicosis on production performance, relative organ weights and biochemical parameters of broiler chickens.